Perlindungan Hukum Bagi Tenaga Kerja Perempun Sebagai SPG (Sales Promotion Girls), Studi Pada Perusahaan Depstore Kota Banda Aceh - Khairani, Khairani; Safarni, Lisna (Universitas Islam Negeri Ar-Raniry, 2019)
Humans are social creatures who cannot live alone and need help from others, therefore humans are required to help each other and cooperate with each other. In terms of hiring other people, Islam through the concept of ijarah law expressly regulates the obligation to provide legal protection to workers. Women especially as SPG (Sales Promotion Girls) in one of the big retail companies in the city of Banda Aceh. The results of this study indicate that the legal protection of labor is reviewed in several aspects, namely the form and work system, wage systems, breaks and leave of these aspects, there are several problems, namely, the obligation of employees to always stand up, if a loss occurs, it is borne by the employee, if sick is not treated, work time is not in accordance with the contract, the salary provided is not in accordance with the quality of work, salary deductions are unclear and without the knowledge of the employee and the company's neglect of the prayer schedule of the employees Dalam praktiknya terdapat banyak pertentangan dan ketidak sesuaian perlindungan hukum terhadap pekerja perempuan khususnya jika ditinjau menurut prinsip-prinsip hukum Islam khususnya dalam konsep Ijarah dalam Fikih Muamalah, ketidaksesuaian itu terdapat dalam beberapa aspek yaitu: kewajiban karyawan untuk selalu berdiri, jikalau terjadi kehilangan maka ditanggung oleh pihak karyawan, kalau sakit tidak diizinkan untuk pulang, waktu kerja tidak sesuai dengan kontrak, gaji yang diberikan tidak sesuai dengan kualitas kerja, pemotongan gaji tanpa sepengetahuan karyawan dan pengabaian perusahaan terhadap jadwal shalat para karyawan. Saran kepada perusahaan retail adalah untuk selalu memenuhi hak pekerja, dan kepada pekerja untuk memenuhi kewajibannya.